A Clever Approach to Measure Organizational Performance: An Overview - Farooq, Rayees (Prabandhan: Indian Journal of Management, 2015)
If organizations cannot appraise their performance, they cannot manage their businesses. The traditional approach to organizational performance has been to consider profitability, which is normally regarded as return on investment. However, the study has provided a thorough view of organizational performance. Therefore, performance measurement literature has been reviewed; which has focused on various approaches such as the performance prism, the balanced scorecard (BSC), the performance pyramid, and the triple bottom line. The study has discussed the multi-dimensionality of organizational performance and suggests that organizations need to incorporate both dimensions of organization's performance (subjective and objective). The main purpose of the study was to provide a holistic view of various approaches with respect to organizational performance.